Meckel Gruber Syndrome: a rare case report - Verma, Manish; Sharma, Shruti; Suthar, Kiran; Thada, Beena (International Journal of Contemporary Pediatrics, 2017)
Meckel gruber syndrome or dysencephalia splanchnocystica, is a rare autosomal recessive disorder caused by failure of mesodermal induction. Worldwide incidence of MGS is 1 per 13,500-140,000 live births. It is characterized by triad of occipital Meningoencephalocele, polycystic kidneys and post-axial polydactyly. Most fetuses affected with this syndrome die before birth due to oligohydramnios, renal failure or pulmonary hypoplasia. We report a rare case of MGS who delivered live at birth with classical features.